2008
DOI: 10.1080/00015458.2008.11680315
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Surgical Treatment of Pancreatic Cancer

Abstract: The study has shown the value of conducting both curative and palliative resection for QoL. Bypass procedures should be performed in cases of non-resectable pancreatic cancer with accompanying jaundice and/or gastric outlet obstruction in patients with a life expectancy of at least 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 0 publications
2
43
0
Order By: Relevance
“…EORTC QLQ-C30 consists of five functional scales with questions related to physical, role, emotional, cognitive and social functioning, a series of symptom scales specific for fatigue, pain, nausea and vomiting, appetite loss, sleep disturbance, dyspnea, constipation, diarrhea, and financial impact, and a global QoL scale. High scores in functioning scales represent a high level of functioning, while high scores in symptom scales represent a high level of symptoms [10,11,12,13,14]. Especially designed for patients with pancreatic cancer, QLQ-PAN26 consists of several items on pain, diet and digestion, fulfillment for healthcare, etc., and a high score indicates severe symptom suffering, while a low score indicates mild or no symptom suffering [15].…”
Section: Methodsmentioning
confidence: 99%
“…EORTC QLQ-C30 consists of five functional scales with questions related to physical, role, emotional, cognitive and social functioning, a series of symptom scales specific for fatigue, pain, nausea and vomiting, appetite loss, sleep disturbance, dyspnea, constipation, diarrhea, and financial impact, and a global QoL scale. High scores in functioning scales represent a high level of functioning, while high scores in symptom scales represent a high level of symptoms [10,11,12,13,14]. Especially designed for patients with pancreatic cancer, QLQ-PAN26 consists of several items on pain, diet and digestion, fulfillment for healthcare, etc., and a high score indicates severe symptom suffering, while a low score indicates mild or no symptom suffering [15].…”
Section: Methodsmentioning
confidence: 99%
“…Kuhlmann et al previously same study population 11 . Kostro et al 12 reported an improvement in emotional and physical status after PR relative to DLB and more gastro-intestinal problems after DLB (without showing scores on individual scales), and recommended PR over DLB for palliative care. Results from our previous study 11 and the current study are contrary to those observations.…”
Section: Quality Of Life After Pr and Dlbmentioning
confidence: 99%
“…Knowledge of QoL after surgical palliation for pancreatic cancer is limited 19,20 , there are limited number of direct comparisons of QoL after PR and DLB 9,11,12 , and investigation of QoL has not been standardised. Kuhlmann et al previously same study population 11 .…”
Section: Quality Of Life After Pr and Dlbmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in patients operated on for malignant disease, the QoL may also be impaired by recurrence of the disease and the need for adjuvant chemotherapy. The data on clinical outcomes and PROs in patients who underwent PHR for various reasons are based either on a large number of patients enrolled over a long period [45,46] or on a small number of cases enrolled over a short period [28,47,48]. The results of these studies are not conclusive; in patients enrolled over a long period, the survival rate evaluated retrospectively suffers from changes in their care whereas studies carried out over a short period do not have definitive conclusions.…”
Section: Pancreatic Head Resectionmentioning
confidence: 47%